Safety Profile of Nutraceuticals Rich in Coumarins: An Update - Simona Codruta Heghes; Oliviu Vostinaru; Cristina Mogosan; Doina Miere; Cristina Adela Iuga; Cristina Adela Iuga; Lorena Filip (Frontiers Media S.A., 2022)
Coumarins are a family of benzopyrones largely distributed in the natural kingdom, being present in the seeds, fruits, flowers, or roots of various plant species. Natural coumarin compounds are found in significant concentrations in some herbs or spices used as nutraceuticals, but they are also present in cosmetics or household products, due to their pleasant odor. Therefore, an accidental exposure to high doses of coumarins, could lead to the development of harmful effects in some patients. This review summarizes the latest published data from preclinical and clinical studies with natural coumarins, focused on the investigation of general and specific toxicity, with the aim of a better understanding of the safety profile of these valuable compounds. Regulatory aspects concerning the use of natural coumarins in several world regions are also reviewed.